Continuous intravenous infusion of recombinant human endostatin combined with concurrent etoposide plus cisplatin and radiotherapy for treatment of unresectable stage III non-small-cell lung cancer (HELPER): a phase 2, multicentre study. (September 2017) - Zhai, Yirui; Ma, Honglian; Hui, Zhouguang; Zhao, Lujun; Li, Dongming; Liang, Jun; Wang, Xiaozhen; Xu, Liming; Chen, Bo; Tang, Yu; Wu, Runye; Xu, Yujin; et al.
Abstract: Background: Concurrent chemoradiotherapy is the standard treatment for unresectable stage III non-small lung cancer, with frequently unsatisfactory results. We aimed to evaluate the efficacy and safety of the addition of continuous intravenous infusion of recombinant human endostatin (Endostar) to concurrent chemoradiotherapy. Methods: We did this prospective, phase 2 study (HELPER) in patients with inoperable stage III non-small-cell lung cancer (defined by the American Joint Committee on Cancer 7th edn staging system) with an E performance score of 0–2; diagnoses were made on the basis of pathology or cytology results. All enrolled patients received thoracic radiation at doses of 60–66 Gy and continuous intravenous infusions of Endostar (7·5 mg/m 2 per 24h, 120 h continuously, 120 h per cycle; from day −5 to day −1, days 10–13, days 24–28, and days 38–42). Additionally, patients received two cycles of etoposide (50 mg/m 2 ; days 1–5 and days 29–33) plus cisplatin (50 mg/m 2 ; day 1, 8, 29, and 36). The primary endpoint was progression-free survival and the secondary endpoints were objective response, overall survival, local recurrence-free survival, and toxicities. Findings: From November, 2012, to June, 2015, 73 patients were enrolled and 67 patients were evaluable. 56 patients were male and 11 patients were female. The median age was 59 years (range 31–69). Most patients (44, 66%) had squamous cell carcinoma. 27 patients (40%) had stage IIIa disease, and 40 (60%) had stage IIIb disease. Severe adverse events were observed in two patients (one had massive haemoptysis and one had pneumonia). The most common adverse event was leucopenia (96%; 45% were grade 3–4). The complete response was 12% and partial response was 64%. The median follow-up time was 37·1 months (range 20·1–52·1). The median overall survival was 34·7 months (21·9–47·4), progression-free survival was 13·3 months (5·5–21·0), and local recurrence-free survival was 27·1 months. Progression-free survival was 51% at 1 year, 35% at 2 years, and 28% at 3 years, overall survival was 82% at 1 year, 60% at 2 years, and 48% at 3 years, and local recurrence-free survival was 73% at 1 year, 55% at 2 years, and 50% at 3 years. Interpretation: For patients with unresectable stage III non-small-cell lung cancer, continuous intravenous human recombinant endostatin in combination with concurrent chemoradiotherapy is an effective treatment with tolerable toxicities. A phase 3 study is warranted. Funding: None.